Peningkatan kemampuan kognitif pada remaja melalui layanan informasi - Cindy Marisa; Evi Fitriyanti (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2019)
Individual cognitive abilities become a benchmark in making decisions to act. High cognitive abilities can provide the potential for success in individuals in various ways, including in their teens. Various kinds of methods are carried out on adolescents so that they are able to maximize their potential so that they develop properly. Information counseling services provide a number of information to clients so that clients are able to process the information and use it as needed. In information counseling services, a number of cognitive activities are carried out so that in addition to adding a number of knowledge and insights, they also develop adolescent cognitive abilities. Based on these assumptions, we conduct research aimed at observing the improvement of adolescent cognitive abilities through information counseling service activities. We conducted an experiment involving 35 teenagers. Based on the results of data analysis, a significant increase in the cognitive abilities of adolescents is presented before and after information counseling services are provided. With an average difference of 20,029. Thus, counselors can provide information counseling services to improve the cognitive abilities of adolescents both at school and outside of school